Tetanus in Sheep - Evaluation of New Successful Treatment Strategy - Tonial Grazziotin, Anna Ritta; Kuwer Jacobsen, Tainã; Henrique Soares, Eduardo; De Bastiani, Grasiela; Fraga e Silva Raimondo, Raquel (Acta Scientiae Veterinariae, 2025)
Background: Tetanus, caused by the neurotoxin of Clostridium tetani, is a significant bacterial disease in sheep. Outbreaks are frequently observed following invasive procedures, such as shearing, ear tagging, and castration, which disrupt the skin’s integrity and create entry points for the anaerobic bacteria. Tetanus toxin inhibits inhibitory neurotransmitters within the central nervous system at sensory receptors and neuromuscular junctions, leading to muscle rigidity, spasm, and eventual paralysis. While the standard treatment regimen encompasses the administration of antibiotics, antitoxins, and supportive therapy, the overall prognosis for tetanus remains guarded. Cases: This report details 2 cases after an outbreak of tetanus within a flock of 7 female Suffolk sheep, each approximately 3 years old and weighing 45 kg, located on a farm ranch in the Rio Grande do Sul which is the southernmost state of Brazil. Tragically, the outbreak resulted in the deaths of 5 animals, underscoring the severity and rapid progression of the disease. The 3 remaining sheep were subsequently transported to the Large Animal Clinic of the Veterinary Medical Teaching Hospital (HCV) of the Universidade Federal do Rio Grande do Sul (CGA-UFRGS) in Porto Alegre city for urgent treatment. The 1st sheep arrived at the clinic, presenting with severe clinical signs indicative of advanced tetanus, including lateral recumbency, pronounced muscle rigidity affecting all limbs and the head, and sialorrhea. Due to the animal’s poor prognosis and the severity of its condition, euthanasia was deemed the most humane course of action. The 2 remaining sheep exhibited varying neurological involvement, with clinical signs ranging from subtle head tilting and pelvic limb extension to more pronounced muscle stiffness and spasms. Both animals were immediately placed on a comprehensive treatment protocol that combined procaine and benzathine penicillin to combat the bacterial infection, anti-tetanus serum to neutralize circulating toxins, midazolam and acepromazine for sedation and muscle relaxation, methocarbamol for further muscle relaxation, and supportive care to address nutritional and hydration needs. Notably, in a novel therapeutic approach, 1 of the sheep received intrathecal administration of anti-tetanus serum to directly target toxins within the CNS, aiming to mitigate the pronounced neurological symptoms. Both animals responded favorably to the treatment strategy. They were subsequently discharged in good health, with no reported relapses or complications due to the procedure or treatment reported by the owner. Discussion: Tetanus outbreaks in sheep can rapidly escalate, with the progression of clinical signs reflecting the advancing neurological damage caused by the tetanus toxin. The presence of tachycardia and tachypnea, coupled with progressive neurological symptoms such as head tilting, limb extension, and muscle spasms, indicates the necessity of prompt and aggressive intervention. In this case, the intrathecal administration of tetanus antitoxin proved to be a critical component of the successful treatment strategy. By directly targeting the toxins within the central nervous system, this approach supplemented the standard systemic treatment and effectively reversed the neurological symptoms observed in the most affected sheep. While tetanus is often associated with a high mortality rate in small ruminants, this case report demonstrates that combining standard therapy with intrathecal antitoxin administration can significantly enhance survival rates, as commonly observed in equine medicine. The positive outcome also underscores the importance of early diagnosis, aggressive treatment, and the potential for broader application of this technique in treating tetanus in sheep. Keywords: Clostridium, tetanus, sheep, intrathecal, methocarbamol.